Associations between BMI and visual impairment of 33 407 preschool children in Germany: a pooled cross-sectional study. (28th October 2020) - Liu, Weina; Schwertz, Rainer; Welker, Andreas; Welker, Judith; Chen, Simiao; Dambach, Peter; Marx, Michael
Abstract: Background: Prevalence of overweight and obesity in Germany is increasing. High body weight can affect children's growth and development. This paper aimed to determine the association between body mass index (BMI) and visual impairment among preschool children and explore the potential role of obesity in predicting visual developmental disorder. Methods: Six consecutive years of data from the School Entry Examination were collected for all preschool children aged from 4 to 6 years residing in Rhine-Neckar County and the City of Heidelberg, Germany from 2013 to 2018. Univariate and multivariate regression were used to analyze the complete data, multiple imputation was used to deal with missing data. Results: Among the group with an immigrant background, children with obesity [OR = 1.20, 99% (1.02–1.42)] were more likely to have visual impairment compared to those with normal body weight ( P  <   0.01) after adjusting for survey year, age, and gender of children, education and occupation of parents, screen time-frequency, whether a television was in their bedroom, and quality of preschool outdoor environment. Conclusion: There were significant associations between obesity and visual impairment among German preschool children with immigrant backgrounds. Strategies to support vulnerable groups were needed across all regional schools.